Compromissos de irmandades mineiras : técnicas, materiais e artífices (c-1708-1815) - Walmira Costa (2016)
This text derives from a study on the materiality of handwritten engagements of religious brotherhoods produced in the captaincy of Minas Gerais between 1708 and 1815. In the sources consulted by Caio César Boschi, 61 engagements were found out and identified in his book Laymen and Power: Laic Brotherhoods and Colonization Policy in Minas Gerais, 1986.This research adds to this file 104 more engagements, kept in archives in Portugal and Brazil, most of them in the state of Minas Gerais. The results obtained unveiled a relevant set of watermarks, names of paper manufacturers, traders and writing materials, as well as pigments used to decorate a rich documental heritage produced by hands still unknown to historiography. It was also discovered that the iconography represented in those engagements was resignified since the printed matters and calligraphy handbooks published in Europe in the 18th century. Furthermore, the primary sources showed up that the apothecaries were “painters’s cooks”, which happens to broaden in a certain way the definition given to those professionals by French lexicographer living in Portugal Rafael Bluteau who defined them as “physicians’s cooks”. The abbreviations and chemical symbols used by physicians and surgeons to write medical prescriptions were also known to those apothecaries, who didn’t work in an arbitrary way as litterature states, but with suitable knowledge. Apart from selling pigments, they also supplied paints to different people in the districts of Sabará and Ouro Preto. Painters such as Manoel da Costa Ataíde and Manoel Ribeiro Rosa were their clients and a list of painting materials of the latter was found on vouchers and orders consulted in the field. The craftsmen responsible for the production of the engagements analysed in this research used silk, leather, velvet and linen to bind them and, to decorate them, pigments like vermillion, azurite, malachite, verdigris, gold and silver leaves, brass, white lead, iron-based writing ink and lacquer in yellow and red colors.